Penerapan model pembelajaran numbered head together (NHT) untuk meningkatkan motivasi belajar dalam pembelajaran IPS pada peserta didik kelas IV sekolah dasar - Asri Widyas Febrianti; Siti Istiyati; Yulianti Yulianti (Universitas Sebelas Maret, 2020)
The purpose of this research is to increase learning motivation in social science learning by applying Numbered Head Together learning model. The type of this research is Classroom Action Research with two cycles action and each cycles had 4 stages that is planning, action, observation, and reflection. The subjects of this research were students of the 4th students at SD Negeri Pajang IV Surakarta in the 2019/2020 academic year with total 26 students. This research uses data collection techniques in the form of interview, observation, questionnaire, and documentation. This research used Miles and Huberman interactive analysis models for the data analysis. The result of the research after applying the model was increased from the first condition 19% to 46% in the first cycle, 83% in the second cycle in classical. The result of the research, the conclution is the learning motivation in social science learning of grade 4th students at SD Negeri Pajang IV Surakarta in the 2019/2020 academic year can be increased after implementation of Numbered Head Together learning model.